1988
DOI: 10.1084/jem.168.6.2031
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1-induced, T cell-mediated regression of immunogenic murine tumors. Requirement for an adequate level of already acquired host concomitant immunity.

Abstract: Intraperitoneal injection of human rIL-1 in a dose of 0.5 microgram daily for 5 d, or 1 microgram daily for 3 d, was capable of causing complete regression of immunogenic SA1 sarcoma growing subcutaneously in syngeneic or semisyngeneic mice. Higher doses of IL-1 were not more therapeutic against the SA1 sarcoma, but needed to be given to cause complete regression of the immunogenic L5178Y lymphoma. On the other hand, the P815 mastocytoma was much less responsive to IL-1 therapy, in that it failed to undergo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…FLC-injected bgibg micc only when these mice received a sufficient number of immune T cells is reminiscent of the results obtained by North et al (1988). They found that the anti-tumor effect of interleukin 1 (IL-I) was most cffcctive against certain tumors by augmenting the "generation or expression of an ongoing T-cell-mediated concomitant immunc responsc" (North et al, 1988). IL-1 was not effective against the immunogenic SA1 sarcoma in T-cell-deficient mice unless these mice were first infused with CD: and CD; T cells from donor mice bearing thc established SA1 sarcoma (North et al, 1988).…”
Section: Discussionmentioning
confidence: 68%
“…FLC-injected bgibg micc only when these mice received a sufficient number of immune T cells is reminiscent of the results obtained by North et al (1988). They found that the anti-tumor effect of interleukin 1 (IL-I) was most cffcctive against certain tumors by augmenting the "generation or expression of an ongoing T-cell-mediated concomitant immunc responsc" (North et al, 1988). IL-1 was not effective against the immunogenic SA1 sarcoma in T-cell-deficient mice unless these mice were first infused with CD: and CD; T cells from donor mice bearing thc established SA1 sarcoma (North et al, 1988).…”
Section: Discussionmentioning
confidence: 68%
“…All the mice cured by multiple mIL-12 gene electrotransfer alone or combined with radiation were also resistant to secondary challenge, however the same phenomena was observed with mice treated with treatments used as pertinent controls (multiple therapies with electric pulse application or plasmid coding for dsRed combined with tumor irradiation) that resulted in tumors cures, due to their immunogenicity. This indicates that multiple mIL-12 gene electrotransfer alone or combined with irradiation and also treatments used as pertinent controls might have either increased the immunogenicity of SA-1 sarcoma [28,41] (increased tumor antigen availability after radiation induced apoptosis) or stimulated the immune cells (control plasmid coding for immunogenic protein) [34,42,43] leading to a better tumor immunosurveillance and prevention of tumor outgrowth after secondary challenge. Thus, in contrast to the effects of IL-12 on tumor cures its contribution to the long term immunity could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1α injected intramuscularly was effective in reducing the number of lung metastases in mice with Lewis lung carcinoma 46 . Intraperitoneal injection of IL-1β caused complete regression of subcutaneous SA1 sarcoma and L5178Y lymphoma in mice 47 . Because IL-1β lost its therapeutic effects in T-cell deficient mice, it was concluded that IL-1β functions by stimulating T-cell mediated antitumor immunity 47 .…”
Section: Cancer-suppressive Functions Of Il-1α and Il-1βmentioning
confidence: 99%
“…Intraperitoneal injection of IL-1β caused complete regression of subcutaneous SA1 sarcoma and L5178Y lymphoma in mice 47 . Because IL-1β lost its therapeutic effects in T-cell deficient mice, it was concluded that IL-1β functions by stimulating T-cell mediated antitumor immunity 47 . Activated invasive RO1 T-lymphoma cells that displayed short-term IL-1α expression manifested reduced tumorigenicity and could be used to treat mice with lymphoma 48 .…”
Section: Cancer-suppressive Functions Of Il-1α and Il-1βmentioning
confidence: 99%